Kandungan Fitokimia dan Aktivitas Antioksidan Tanaman Waru (Hibiscus tiliaceus L.) - Farendina Suarantika; Vinda Maharani Patricia (Journal of Pharmaceutical and Health Research, 2023)
The mangrove plant (Hibiscus tiliaceus L.) is widely cultivated in tropical regions such as Indonesia because almost all parts of plant are believed to provide many benefits. Som of the benefits of the mangrove plant include laxative, treating earache, antibacterial, and antioxidant. The aim of the research is to analyze the content of phytochemical compounds contained in the mangrove plant and its antioxidant activity. This research uses a journal review method based on data collection carried out by inclusion and exclusion obtained from the google scholar, science direct, taylor and francis, garuda, and sage publication data search engine, including textbooks and scientific articles published above year of 2013. The result of the research is the phytochemical compounds found in mangrove plant are anthocyanin compounds, amides, coumarins, phenols, organic acids and flavonoid compounds that identified in the leaves, stems, and bark in mangrove plants uses several of solvents, there are methanol water, chloroform, and ethanol. The part of the plant that has antioxidant activity is the leaves which has strong antioxidant activity (IC50 = 86,5 µg/mL).